Gender Inequality in the Labor Market in Serbia - Reva, Anna (World Bank, Washington, DC, 2014)
This paper presents a broad overview of labor market indicators for men and women in Serbia with a focus on employment patterns, entrepreneurship and career advancement as well as earnings differentials. The analysis relies primarily on the results of the Labor Force Surveys conducted in Serbia in April 2008 and October 2009. The findings show that although the overall labor market situation in Serbia is difficult, women are in a much more disadvantageous position than men. Women are much less likely to be employed, start a business or advance in the political arena. Furthermore, there is a significant wage gap between men and women in a number of sectors and occupational groups with low educated women being particularly disadvantaged. The results of the Oaxaca-Blinder decomposition demonstrate that the wage gap is indicative of discrimination of women in the labor market as earnings differentials cannot be explained by differences in observed characteristics of male and female employees. Based on the obtained results, the paper outlines four broad areas that require the attention of policy-makers: employment generation; enhancement of education outcomes; improvement of the regulatory environment and support to women's business and political careers; and promotion of transparent performance setting mechanisms.